Mitigating crisis impact: The influence of corporate social responsibility on non-financial firms' financial performance - Alhajjeah, Diana; Besim, Mustafa; Al-Hajieh, Heitham (Elsevier, 2025)
This study investigates the impact of corporate social responsibility (CSR) on the financial performance of firms by analyzing how it affects the relationship between capital structure and financial performance during the COVID-19 pandemic. We focus on non-financial publicly listed firms in the USA, UK, Canada, Japan, and Italy from 2018 to 2021. Our findings reveal that during the pandemic short-term debt significantly negatively impacts return on assets (ROA), specifically a decrease of 35 %. Additionally, we provide empirical evidence that CSR positively influences financial performance. In particular, the combined CSR scores, as well as environmental and social activities, positively affect ROA, return on equity (ROE), and Tobin's Q across all analyses. We observe that a high combined score (ESG) mitigates the adverse effects of all types of debt on ROA and ROE. However, the positive impact on Tobin's Q is more pronounced regarding longterm and total debt by 0.987 % and 0.937 %, respectively. Furthermore, our analysis indicates that high environmental, social, and governance activities have a more substantial positive effect on the relationship between total debt and both ROE and Tobin's Q. Overall, our study suggests that investing in CSR can be a wise strategy for firms, not only helping to alleviate the adverse effects of debt during market downturns but also switch the adverse effect to positive which ultimately enhancing financial performance.
Keywords: Corporate financial performance; Capital structure; Corporate social responsibility; System generalized method of moments; COVID-19